Inputs Quality: A Quality Assurance Process in Enhancing Effectiveness of Public Secondary Schools in Ilorin West Local Government Secondary Schools, Kwara State - Sulyman, Kamaldeen Olohundare; Lawal, Abdulmumin Abubakar; ADIGUN , Oluyemisi Abimbola; Abdulrauf , Busirat Iyabo (International Journal of Educational Management, 2022)
It is one thing to have educational inputs available in the school system but it is another thing entirely to ensure that the inputs are qualitative. Hence, this study examined inputs quality: A quality assurance process in enhancing effectiveness of Ilorin West Local Government secondary schools, Kwara State. The study adopted a descriptive design of survey type. The population for the study comprised 1,541 teachers in the entire 33 public secondary schools in the Local Government Area. Random sampling technique was used to select 20 schools. Also, random sampling technique was used to select 308 teachers using Krejcie and Morgan (1970) table for determining sample size while purposive sampling technique was used to select principals and vice principals (academics) of the sampled schools.Inputs Quality Questionnaire (IQQ) and proforma were used to collect data for the study. The questionnaire was validated and found reliability coefficient of 0.76, using Cronbach’s Alpha. The hypotheses generated in the study were tested using Pearson Product-Moment Correlation Statistic at .05 level of significance. The study concluded that ensuring quality of the inputs such as teachers, students and physical facilities plays significant roles in enhancing effectiveness of Ilorin West Local Government secondary schools, Kwara State. Based on the findings and conclusion, it was recommended that, government should ensure adequate supply of quality teachers and physical facilities to schools and parents should give their children adequate academic support right from basic schools make to them function properly as inputs in secondary schools, to enhance actualization of effectiveness.